2022
DOI: 10.1001/jamainternmed.2022.1903
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Bias in Pulse Oximetry and Clinical Outcomes

Abstract: Assessment of blood oxygen saturation is an important measure of health on which many diagnostic and treatment decisions are based. Blood oxygen saturation is most commonly assessed via pulse oximetry, with increasing use across the home, clinic, and hospital settings during the COVID-19 pandemic. 1 However, inaccuracies in pulse oximetry measurement have come under scientific scrutiny over the past 2 years. [2][3][4][5][6] Professional organizations, lawmakers, and the public have actively engaged with the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…Large integrated health systems such as the Veterans Health Administration and NHS could have a role to purchase and use only pulse oximeters proven to provide equivalent accuracy in black patients rather than devices of unproven equity. 33 34 …”
Section: Discussionmentioning
confidence: 99%
“…Large integrated health systems such as the Veterans Health Administration and NHS could have a role to purchase and use only pulse oximeters proven to provide equivalent accuracy in black patients rather than devices of unproven equity. 33 34 …”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study of healthy volunteers, we have found that low perfusion interacts with both medium and dark skin pigment to substantially increase pulse oximeter bias. For subjects with dark skin and low perfusion, these errors lead to missed hypoxemia diagnoses at frequencies comparable to or higher than those reported for Black hospitalized patients in retrospective clinical studies 9-12 . Because critical illness is commonly associated with low peripheral perfusion, this finding may be of significant clinical importance.…”
Section: Discussionmentioning
confidence: 74%
“…For subjects with dark skin and low perfusion, these errors lead to missed hypoxemia diagnoses at frequencies comparable to or higher than those reported for Black hospitalized patients in retrospective clinical studies [9][10][11][12] . Because critical illness is commonly associated with low peripheral perfusion, this finding may be of significant clinical importance.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations